Clinical impact of sarcopenia on gastrointestinal tumors - Pereira, Ana (2021)
Preoperative risk stratification in cancer surgery is important to improve treatment and outcome. Sarcopenia is defined by progressive and generalized loss of skeletal muscle mass and strength and is now getting attention as a poor prognostic factor. The purpose of this review was to explore the impact of sarcopenia on short and long-term outcomes in patients undergoing surgical resection of gastrointestinal tumors. Recent studies suggest that sarcopenia contributes to postoperative complications and overall survival. The relatively simple evaluability, as well as its modifiable nature, provides an intriguing potential for sarcopenia to be included in standard preoperative clinical evaluation. Such evaluations can provide physicians with important information to target high-risk individuals with prophylactic measures and eventually improve surgical outcomes.